Patterns of obsessive-compulsive symptoms and social functioning in schizophrenia; a replication study. (January 2019) - Swets, Marije; van Dijk, Floor A.; Schirmbeck, Frederike; Peen, Jaap; de Haan, Lieuwe; Alizadeh, Behrooz Z.; van Amelsvoort, Therese; Bartels-Velthuis, Agna A.; van Beveren, Nico J.; Bruggeman, Richard; Cahn, Wiepke; Delespaul, Philippe; et al.
Highlights: Applying cluster analysis, Lysaker et al. (2004), identified different subgroups of schizophrenia patients with and without OCS, those with relatively high social functioning and those with relatively low social functioning. The current study is a replication approach in a large representative cohort of patients with psychotic disorder with cross-sectional and longitudinal assessments. Similar to the study ofLysaker et al. (2004) cluster analysis formed subgroups differing in the presence of OCS and social functioning. In the current study the following five clusters were identified: an OCSneg/HF (no OCS/ high functioning) group, an OCSneg/PF (no OCS/poor functioning) group, an OCSmild/HF (mild-OCS/ high functioning) group, an OCSmild/PF (mild-OCS/ poor functioning) group and an OCShigh/MF (high-OCS/ moderate functioning) group. In line with the study ofLysaker et al. (2004), the OCSmild/HF group showed less negative symptoms than the poor functioning groups. However, in contrast to the original study, the group with OCS and poor functioning did not differ in executive functioning or sustained attention compared to the other groups. Results support the idea that co-morbid OCS can have different implications for different subgroups of patients. Abstract: Research has found that Obsessive Compulsive Symptoms (OCS) in schizophrenia are associated with either more or less negative symptoms and either better or poorer cognitive functioning. In order to explain these contradictory results, (Lysaker et al., 2004 ), performed a cluster analysis resulting in 2 OCS positive (OCSpos) clusters, one with higher functioning (HF) and one with poorer functioning (PF) compared to 2 OCS negative (OCSneg) clusters. The OCSpos/HF cluster had less negative symptoms compared to all other clusters, while the OCSpos/PF cluster showed poorer executive functioning. We performed a replication study, in an almost 10 times larger, representative sample, using both a longitudinal and cross-sectional design. Similar to Lysaker et al., we found a group with mild OCS and HF (OCSmild/HF) showing less negative symptoms compared to the PF groups. We also found an OCSmild/PF group, which did not significantly differ in executive functioning from the other groups. Moreover, we did not find evidence for a better prognosis in the OCSmild/HF group, and thus found no support for the assumption that for some patients OCS might be an effective coping mechanism.